2017
DOI: 10.1111/cmi.12730
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical inflammasomes: Antimicrobial defense that does not play by the rules

Abstract: Although much research has focused on defining the actions of caspase-1 containing canonical inflammasomes in promoting host defense, noncanonical inflammasomes have received comparatively little attention. Exciting new concepts have recently emerged detailing their atypical mechanism of activation, importance in defending against cytosolic Gram-negative pathogens, and role in innate immune defenses of nonmyeloid cells, which has revamped interest in the study of noncanonical inflammmasomes. Here, we will disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 74 publications
(221 reference statements)
0
23
0
Order By: Relevance
“…Furthermore, colonic tissue explants from C. rodentium -infected caspase-11 -deficient mice also had decreased IL-18 secretion ( 160 ). This caspase-11-dependent IL-18 processing was proposed to occur in IEC, contrary to the caspase-1-dependent cleavage of IL-18 and IL-1β observed in myeloid cells ( 161 ).…”
Section: Inflammasomes and Cell Death: Pyroptosis And Apoptosismentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, colonic tissue explants from C. rodentium -infected caspase-11 -deficient mice also had decreased IL-18 secretion ( 160 ). This caspase-11-dependent IL-18 processing was proposed to occur in IEC, contrary to the caspase-1-dependent cleavage of IL-18 and IL-1β observed in myeloid cells ( 161 ).…”
Section: Inflammasomes and Cell Death: Pyroptosis And Apoptosismentioning
confidence: 72%
“…The importance of “canonical” and “non-canonical” inflammasomes may vary depending on the nature and characteristics of the pathogenic threat and the cell types involved. For example, upon challenge with flagellin-deficient Salmonella , caspase-1-deficient macrophages died in a similar manner to WT macrophages, whereas caspase-11-deficient macrophages were resistant to cell death ( 158 , 161 ). In contrast, both caspase-1 and caspase-11 were required for cell death in macrophages infected with WT Salmonella ( 158 ).…”
Section: Inflammasomes and Cell Death: Pyroptosis And Apoptosismentioning
confidence: 99%
“…The inflammasome has been shown to play a pivotal role in the inflammatory response by activating the inflammatory caspase caspase‐1, which induces pyroptosis and the secretion of the pro‐inflammatory cytokine IL‐1 β in macrophages. In these inflammasome studies, caspase‐11 was unexpectedly identified as a novel activator of caspase‐1, and the complex of caspase‐11 and intracellular LPS was referred to as the ‘non‐canonical inflammasome’, adding to the diversity of cytoplasmic innate immunity responses in macrophages . Recent studies have not only identified intracellular LPS as agonists of the non‐canonical inflammasome, but also demonstrated that inflammatory caspases, such as a mouse caspase‐11 and human caspase‐4/5, are direct molecular sensors of intracellular LPS and activate non‐canonical inflammasome responses .…”
Section: Discussionmentioning
confidence: 99%
“…In these inflammasome studies, caspase-11 was unexpectedly identified as a novel activator of caspase-1, and the complex of caspase-11 and intracellular LPS was referred to as the 'non-canonical inflammasome', 19 adding to the diversity of cytoplasmic innate immunity responses in macrophages. 86,87 Recent studies have not only identified intracellular LPS as agonists of the non-canonical inflammasome, 21,22 but also demonstrated that inflammatory caspases, such as a mouse caspase-11 and human caspase-4/5, are direct molecular sensors of intracellular LPS and activate non-canonical inflammasome responses. 23 Intracellular LPS released from the Gram-negative bacterium-containing vacuoles by GBP chr3 -mediated proteolysis are directly detected by caspases-4/5/11, and these caspases are oligomerized and activated, thereby inducing anti-pathogenic inflammatory responses by triggering pyroptosis and secretion of IL-1b and IL-18 in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Other innate detection systems rely on canonical or non-canonical inflammasomes [13,14]. They are induced by PAMP or Danger-Associated Molecular Patterns (DAMP) and lead to the activation of the Caspase-1, which in turn cleaves precursor molecules (e.g., pro-IL-1β and pro-IL-18) to liberate active IL-1β and IL-18 in the infected or endangered microenvironment.…”
Section: Interplay Between Hbv and Innate Immunity: Basic Insightsmentioning
confidence: 99%